Strategy Based Making Instruction Management Information Framework (EMIS) - Aya, Ayumi; Emi, Chieko (Pandawan Sejahtera Indonesia, 2020)
The Education Management Information System (EMIS) is planned for share genuine data like allies of strategy creators. This examination intends to depict and investigate the execution of EMIS in strategy making in the Mapenda zone of ??the Ministry of Religious Affairs region Gunungkidul. The exploration results show that EMIS is compared to a base learning data for strategy making can't yet be utilized viably ideal. EMIS data is utilized distinctly as right on time as essential data cross-check through face to face gatherings or by means of phone correspondence so it requires some investment. The obstruction was that the EMIS information assortment measure was attempted distinctly at specific occasions so the data was not refreshed consequently, EMIS application issues, EMIS the executives skill, and the cooperation of madrasah chiefs in information assortment.